2018
DOI: 10.1016/j.dib.2018.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profile data of phorbol esters biosynthetic genes during developmental stages in Jatropha curcas

Abstract: Jatropha curcas is currently known as an alternative source for biodiesel production. Beside its high free fatty acid content, J. curcas also contains typical diterpenoid-toxic compounds of Euphorbiaceae plant namely phorbol esters. This article present the transcription profile data of genes involved in the biosynthesis of phorbol esters at different developmental stages of leaves, fruit, and seed in Jatropha curcas. Transcriptional profiles were analyzed using reverse transcription-polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…By using SRM and PRM assays, endogenous peptides corresponding to tryptic peptides of gene models Jcr4S01081.10, Jcr4S01081.20, Jcr4S03333.20, Jcr4S03853.10, Jcr4S04129.10, Jcr4S06058.10/Jcr4S01881.20, and the peptide NLIQNIELIDTLR were identified in roots, but not in leaves and endosperm of the HPE and LPE genotypes. Although the expression of CS transcripts in different tissues and developmental stages of J. curcas have been reported [ 9 , 11 , 12 , 14 , 26 , 27 ], no corresponding data on the proteins encoded by the transcripts were produced. Only recently a single proteomics study leads to the identification of CS in roots of J. curcas [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using SRM and PRM assays, endogenous peptides corresponding to tryptic peptides of gene models Jcr4S01081.10, Jcr4S01081.20, Jcr4S03333.20, Jcr4S03853.10, Jcr4S04129.10, Jcr4S06058.10/Jcr4S01881.20, and the peptide NLIQNIELIDTLR were identified in roots, but not in leaves and endosperm of the HPE and LPE genotypes. Although the expression of CS transcripts in different tissues and developmental stages of J. curcas have been reported [ 9 , 11 , 12 , 14 , 26 , 27 ], no corresponding data on the proteins encoded by the transcripts were produced. Only recently a single proteomics study leads to the identification of CS in roots of J. curcas [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, Farias et al (2020) gathered evidence for the presence of CS in the roots of two genotypes displaying contrasting levels of PE [ 25 ]. On the other hand, the literature abound on reports on the transcription of the CS gene in developing seeds [ 26 , 27 ], mature seeds [ 26 , 27 ], developing fruit [ 11 , 14 , 27 ], mature fruits [ 14 ], developing leaves [ 12 , 26 , 27 ], mature leaves [ 9 , 26 , 27 ]; roots [ 9 , 26 ], flowers [ 9 , 26 ], tegmen [ 12 ], and stem [ 9 ]. Unfortunately, none of these results were validated by protein targeted methods and may simply highlight the frequently found poor transcript-protein correlation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on the effect of abiotic stress in Daucus carota L. showed that Actin demonstrated good and stable performance for qPCR analysis in heat, cold, and methyl jasmonate treatment. 59 Moreover, Jadid et al 60 used Actin as the internal standard during gene expression profiling in different vegetative organs of Jatropha curcas . Similar results were reported by Feng et al, 61 who evaluated housekeeping genes in response to abiotic stress in celery ( Apium graveolens L.).…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is a monofunctional class I diterpene synthase found in the Euphorbiaceae (Zerbe & Bohlmann, 2015), and its reaction product (1R,3S‐casbene) is the precursor of a wide range of diterpenoid scaffolds (King et al, 2016; Luo et al, 2016). In J. curcas , although CS mRNA has been found in several fruit tissues and leaves (Jadid et al, 2018), the protein has only been reported in roots (Farias et al, 2020), which is probably closely related to the diversity of diterpenoids found there (Cavalcante et al, 2020). Furthermore, a targeted proteomic analysis revealed that genotypes displaying contrasting levels of PE have similar CS abundance (de Almeida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%